Angiopoietin-Like Protein 3 (ANGPTL3) Inhibitors in the Management of Refractory Hypercholesterolemia - Kosmas CE; Bousvarou MD; Sourlas A; Papakonstantinou EJ; Peña Genao E; Echavarria Uceta R; Guzman E (Dove Medical Press, 2022)
Constantine E Kosmas,1,2 Maria D Bousvarou,3 Andreas Sourlas,3 Evangelia J Papakonstantinou,4 Edilberto Peña Genao,2 Rogers Echavarria Uceta,2 Eliscer Guzman1,2 1Division of Cardiology, Department of Medicine, Montefiore Medical Center, Bronx, NY, USA; 2Cardiology Clinic, Cardiology Unlimited, PC, New York, NY, USA; 3School of Medicine, University of Crete, Heraklion, Greece; 4General Directorate of Public Health and Social Welfare, Athens, Attica Region, GreeceCorrespondence: Constantine E Kosmas, Email cekosmas1@gmail.comAbstract: Cardiovascular disease (CVD) is the most common cause of death in a global scale and significantly depends on the elevated plasma levels of low-density lipoprotein cholesterol (LDL-C) and the subsequent formation of atherosclerotic plaques. While physicians have several LDL-C-lowering agents with diverse mechanisms of action, including statins, ezetimibe, proprotein convertase subtilisin/kexin type 9 (PCSK9) inhibitors and inclisiran, angiopoietin-like protein 3 (ANGPTL3) inhibitors have recently emerged as a powerful addition in the armamentarium of lipid-lowering strategies, especially for patients with refractory hypercholesterolemia, as in the case of patients with homozygous familial hypercholesterolemia (HoFH). ANGPTL3 protein is a glycoprotein secreted by liver cells that is implicated in the metabolism of lipids along with other ANGPTL proteins. These proteins inhibit lipoprotein lipase (LPL) and endothelial lipase (EL) in tissues. Loss-of-function mutations affecting the gene encoding ANGPTL3 are linked with lower total cholesterol, LDL-C, and triglyceride (TG) levels. Evinacumab is a monoclonal antibody that targets, binds to, and pharmacologically inhibits ANGPTL3, which was recently approved by the United States Food and Drug Administration (FDA) as a complementary agent to other LDL-C lowering regimens for patients aged 12 or older with HoFH, based on clinical trial evidence that confirmed its safety and efficacy in those patients. Antisense oligonucleotides (ASOs) also represent an interesting class of agents that target and inhibit the mRNA derived from the transcription of ANGPTL3 gene. This review aims to present and discuss the current clinical and scientific data pertaining to the role of ANGPTL3 inhibitors, a novel lipid-modifying class of agents capable of reducing LDL-C levels via a mechanism independent of LDL receptors.Keywords: cardiovascular disease, ANGPTL3 inhibitors, evinacumab, refractory hypercholesterolemia, familial hypercholesterolemia, LDL-cholesterol, LDL receptors